Representações portuguesas e brasileiras da identidade nacional portuguesa no século XX - Sobral, José Manuel (2010)
The article evaluates racial and non-racial interpretations related to Portuguese national identity in the twenty century, considering their intersections with official state nationalism. The article is based on the work of four intellectuals, both Portuguese and Brazilian, who exerted a major influence on representations about Portuguese national identity: Mendes Correia, Gilberto Freyre, Sérgio Buarque de Hollanda and Jorge Dias. Investigations about these works highlight relations, affinities and confrontation between texts and their authors, revealing not only changes seen within the intellectual field, but also developments in the definition of official nationalism. The analysis buildup took into consideration not only the context for production of the works but also their distinctive forms of receptivity.